Sistematización del montaje interdisciplinar Transiciones del curso Danza del Caribe 2022-2 (2024)
The present work is a systematization that seeks to collect the experience of the collective creation process of the interdisciplinary work Transiciones, based on the experiences lived in Gamarra, Cesar, by the Master Artists in Training, within the framework of the course Danza del Caribe of the Degree in Performing Arts at the Universidad Antonio Nariño during the period 2022-2. The aim of this document is to create an artistic-pedagogical reflection on the processes of collective creation, based on the experience lived by the Master Artists in Training, as well as to understand the didactics for creation with large groups, with the objective of generating methodological strategies that will contribute to the Master Artists in Training for future works of collective creation.